Reading Motivation and EFL Learners’ Vocabulary Development Against Interest in Learning English Moderated by Teacher Competence - Muhalida Zia Ibhar (UIR Press, 2022)
Reading is critical for students of English as a foreign language. Apart from the four abilities that needed desire to grow, reading is one of the most critical skills in language acquisition. Therefore, this study aims to investigate reading motivation and EFL learners’ vocabulary development against interest in learning English moderated by teacher competence. The research participants were university students (ages 18) as many as 53 students in the Riau Province, Indonesia. This research was using quantitative methods. The data were collected using a questionnaire and analyzed using the SEM (Structural Equation Modeling) technique which was operated through the Warp PLS 3.2.7 program. Finding of this study revealed that there was a significant effect on student interest in learning with teacher competence as a moderating variable. The teacher should provide an interesting text for students, especially EFL students, so that students read the English text not because they are forced by their surroundings, but because they have an internal motive to complete the work.